Answer:
Tom is 15 years old and Jean is 9 years old
Explanation:
Let call:
x: the age of Tom
y: the age of Jean
From the sentence: three years ago Tom was twice as old as Jean, we get the first equation:
(x-3)=2(y-3)
Solving for x:
x=2y-6+3
x=2y-3
From the sentence: in two years the sum of their ages will be 28 years, we get the second equation:
(x+2)+(y+2)=28
Solving:
x+y+4=28
x+y=28-4
x+y=24
Now, we have two equations with two incognites:
equation 1: x=2y-3
equation 2: x+y=24
For finding the values of x and y we need to replace the x = 2y-3 on the second equation and solve for y, as following:
(2y-3)+y=24
2y+y-3=24
3y=27
y=27/3
y=9
Then, we Replace y=9 on the first equation and get:
x=2(9)-3
x=18-3
x=15
Now, we have the values of x and y that satisfy the two formulate equation, so the answer is x equal to 15 and y equal to 9. So, Tom is 15 years old and Jean is 9 years old